Selection of Wild Plant Species from Organic Rice Field in Sumberngepoh Village in Malang as Attractant of Trichogramma spp. (Hymenoptera, Trichogrammatidae) - Wahyu Kusumayanti Putri; Bagyo Yanuwiadi (Indonesian Journal of Environment and Sustainable Development, 2014)
One of the actions in biological control is the use of parasitoid. Some wild plant species can attract those parasitoid. By the fact, the objective of this research are to select some of wild plant species attracting Trichogramma spp. These wild plant were belong to Asteraceae (Eupatorium odoratum, Bidens pilosa, Crassocephalum crepidioides) and Mimosaceae (Parkia speciosa, Leucaena glauca, Mimosa pudica). Mass rearing of trichogramma spp. was prepared for those purpose. The selection were conducted by using four armed olfactometer. The percentage of the tested Trichogramma spp. attracted to the wild plant species was noted as well as their orientation duration to select the plant species. The difference of the mean of their orientation duration was analyzed statistically by T-Test. Both of plant familia can attract the parasitoid. This were the plant species that attracted Trichogramma spp. From the most attractive to the lowest one : B. pilosa 22 %, E. odoratum 18.6 %, M. pudica 18.2 %, C. crepidioides 13.8 %, P. speciosa 13.6 %, and L. glauca 13.6 %. For the orientation duration, this are the plant species that can attract the parasitoid from the fastest one to the slowest one : P. speciosa 45.5 seconds, C. crepidioides 46.2 seconds, L. glauca 49 seconds, E. odoratum 50.6 seconds , B. pilosa 53.4 seconds, and M. pudica 55.2 seconds.Keywords : Asteraceae, Mimosaceae, Trichogramma spp.